Agronomic performance of ‘Bourbon’s’ group coffee plants populations - de Lima, Amador Eduardo; Mendes, Antônio Nazareno Guimarães; Carvalho, Gladyston Rodrigues; Botelho, César Elias; Castro, Elisa de Melo; Cardoso, Diego de Abreu (Coffee Science - ISSN 1984-3909, 2016)
The coffee breeding research influences directly to the obtainment of coffee trees more productive. The purpose of this study was to evaluate the agronomic characteristics of the Bourbon coffee group plants, in two coffee growing regions of Minas Gerais state, aiming at the populations selection with high productivity, adapted and stable. In experiment consisting of 20 treatments were evaluated 17 populations of Bourbon’s coffee group, and three cultivars widely cultivated in Brazil. We used a randomized block design (RBD) with three replicates, each plot consisted of ten plants. We evaluated the characteristics of bean yield, percentage of beans retained in sieve size 16, vegetative vigor and adaptability and stability in yield (Lavras, Três Pontas e Patrocínio). The populations studied have greater yield potential in South of Minas Gerais, carried out in the counties of Lavras and Três Pontas. The populations 05 (Bourbon Amarelo - Faz. Boa Vista / Campos Altos – MG), 17 (Bourbon Amarelo - Faz. Monte Alegre - Talhão Limoeiro / Alfenas - MG) and 19 (Catuaí Vermelho IAC 144 - Faz. Experimental de Machado - MG), are more productive, adapted and stable. The high productive and good agronomic characteristics by this populations of Bourbon, shows that populations have high potential for genetic selection.